ANALISIS OPEN-ENDED PROBLEM SEBAGAI PENILAIAN MATEMATIKA SELAMA PEMBELAJARAN DI ERA PANDEMIC COVID-19 - Iman Solahudin (Department of Mathematics Education, Universitas Kuningan, 2022)
The COVID-19 pandemic has had an impact on Indonesia's education process, which was originally done offline, turned into online, as a result, teachers have difficulty assessing learning outcomes. Open-ended questions are expected to be an alternative in conducting assessments and help analyze students' creativity, reasoning, and mathematical thinking processes. This study aims to analyze Open-Ended in conducting assessments during the Covid-19 Pandemic using a descriptive approach through a case study in a school in Cirebon Regency. The subjects in this study were 2 respondents. Data was collected through a test giving questions about the Open-Ended Problem. Based on the application of two open-ended questions, it was found that all students gave answers correctly, in different ways based on their mathematical knowledge and abilities. Through problem solving by students, creativity, reasoning, and thought processes can be seen from the answers they take. The results of the analysis of all students were able to meet the Open-Ended Problem indicator, although one of the students had a slight deficiency in solving the problem, he did not show his full knowledge, it was seen from the way the explanation of the answer was still not clear. So, presenting open problems is very effective in online learning, students find it difficult to solve problems that have various solutions.